DETERMINANT MEAN YEARS OF SCHOOLING IN CENTRAL JAVA - Lestari, Dina Hernita; Setyadharma, Andryan (Efficient: Indonesian Journal of Development Economics, 2019)
The purpose of this research is to determine factors that affect mean years schooling in Central Java between 2014-2017. The data used in this research is panel data. The panel data consists of time series data (2014-2017) and cross section data (35 districts/cities in Central Java). The variables used in this research are dropouts school rate, child labor, BOS fund allocation, per capita income, and poverty rate. The results of this research indicate that: dropouts school rate has insignificant effect on MYS, child labour has a negative and significant effect on MYS, BOS has insignificant effect on MYS, per capita income has a positive and significant effect on MYS, poverty rate has a negative and significant effect on MYS. Based on the results of this research, it is suggested that: (1) The local goverment need to do coordination regulary with related institute; (2) First before other things, finish the poverty problems so the child labor will be decreased; (3) The government needs to maximize work programs other than BOS fund allocation such as the Poor Students Program (BSM) and the Smart Indonesia Card (KIP); (4) The increasement of human welfare will improve the capability to defray education tp the next level; (5) The goverment must maximize more the work program that have been made such as the BSM and KIP programs so it can be reached by children from the poor family.   Tujuan dari penelitian ini adalah untuk mengetahui faktor-faktor yang mempengaruhi rata-rata masa sekolah di Jawa Tengah antara 2014-2017. Data yang digunakan dalam penelitian ini adalah data panel. Data panel terdiri dari data deret waktu (2014-2017) dan data penampang (35 kabupaten / kota di Jawa Tengah). Variabel yang digunakan dalam penelitian ini adalah angka putus sekolah, pekerja anak, alokasi dana BOS, pendapatan per kapita, dan tingkat kemiskinan. Hasil penelitian ini menunjukkan bahwa: tingkat putus sekolah berpengaruh tidak signifikan terhadap MYS, pekerja anak memiliki efek negatif dan signifikan terhadap MYS, BOS memiliki efek tidak signifikan pada MYS, pendapatan per kapita memiliki efek positif dan signifikan terhadap MYS, tingkat kemiskinan memiliki efek negatif dan signifikan pada MYS. Berdasarkan hasil penelitian ini, disarankan agar: (1) Pemerintah daerah perlu melakukan koordinasi secara teratur dengan lembaga terkait; (2) Pertama sebelum hal-hal lain, selesaikan masalah kemiskinan sehingga pekerja anak akan berkurang; (3) Pemerintah perlu memaksimalkan program kerja selain alokasi dana BOS seperti Program Siswa Miskin (BSM) dan Kartu Indonesia Pintar (KIP); (4) Peningkatan kesejahteraan manusia akan meningkatkan kemampuan untuk membiayai pendidikan ke tingkat berikutnya; (5) Pemerintah harus memaksimalkan lebih banyak program kerja yang telah dibuat seperti program BSM dan KIP sehingga dapat dijangkau oleh anak-anak dari keluarga miskin.